Achondroplasia: Case Report and Review of Literature - Shah, GS; Shrivastava, MK; Shah, D; Gupta, N (Journal of Nepal Paediatric Society, 2011)
A two month old male child presented to emergency of B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan and was admitted to Paediatric ward with history of fever, cough and respiratory distress. On examination the breathing was rapid and shallow. The child was small for age with an upper to lower segment ratio of 1.9. The anteroposterior diameter of thorax was reduced. We report a very rare case of achondroplasia which was recognized in a two month age child who presented with severe pneumonia. Usually the clinically features of achondroplasia is more prominent when the child is growing in height but we diagnosed it in a two months child after performing the skeletal survey. DOI: http://dx.doi.org/10.3126/jnps.v31i3.5363 J Nep Paedtr Soc 2011;31(3): 216-224-226